Pendidikan Karakter Bersaing dalam Musabaqah Tilawatil Qur’an - Hasan, Abdur Rokhim (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
This article tries to explain that the Qur'an explains a lot about musabaqah, but it is general in nature. Because of his generality, in this case, the writer traces the law and his views through the views of the commentators' scholars. In addition, the author also traces the traditions of the Prophet that explain the recommended reading of the Qur'an with a melodious song and voice. The results of this study prove that musabaqah existed at the time of the Prophet, even the Prophet did. Many scholars believe that the implementation of the Musabaqah Tilawatil Qur’an (MTQ) is permissible, even encouraged. In addition, musabaqoh indirectly has an educational value, namely competitive character education.